Implementasi Pendidikan Karakter Melalui Kegiatan Pembelajaran Di Pondok Pesantren Nurul Imaniyah Kuningan - Putri, Gizka Amalia; Anwari, Hamdan; Suklani, Suklani (Universitas Pakuan, 2025)
IMPLEMENTATION OF CHARACTER EDUCATION THROUGH LEARNING ACTIVITIES AT NURUL IMANIYAH ISLAMIC BOARDING SCHOOL KUNINGANThis study aims to analyze the implementation of character education through learning activities at the Nurul Imaniyah Kuningan Islamic Boarding School. Character education in Islamic boarding schools is considered strategic in facing various moral challenges of adolescents, so an empirical study is needed regarding the practice, supporting and inhibiting factors, and its impact on students. The study used a qualitative approach with a case study method and data collection through interviews, observation, and documentation. Analysis was conducted using the Miles and Huberman model through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of character education is carried out holistically through the integration of formal learning such as the study of yellow books that instill moral values, etiquette, patience, and obedience with non-formal activities such as halaqah, muhadarah, and habituation of worship that strengthen intellectual, social, and spiritual character. The main supporting factors include the exemplary behavior of kyai and ustadz, structured activities, and collaboration with parents, while several inhibiting factors arise from the diversity of student backgrounds, limited infrastructure, and a lack of teaching staff. Overall, character education at this Islamic boarding school has a significant impact on forming students who are noble, disciplined, independent, and have integrity.